2010
DOI: 10.1111/j.1469-7610.2010.02256.x
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to potentially traumatic events in early childhood: differential links to emergent psychopathology

Abstract: Objective To examine associations between exposure to potentially traumatic events (PTEs) and clinical patterns of symptoms and disorders in preschool children. Method Two hundred and thirteen referred and non-referred children, ages 24 to 48 months (MN = 34.9, SD = 6.7 months) were studied. Lifetime exposure to PTEs (family violence and non-interpersonal events) and recent stressful life events were assessed with the Preschool Age Psychiatric Assessment (PAPA) and Child Life Events Scale. Child psychiatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
1
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(119 citation statements)
references
References 33 publications
6
103
1
2
Order By: Relevance
“…Several studies using a person-centered approach have identified different profiles of adjustment among children and adolescents exposed to IPV, showing that between 15% and 60% of these population present profiles of resilience in absence of adjustment problems [33][34][35][36][37][38][39]. Across studies, the most significant and consistent factors discriminating between profiles of resilience and psychopathology in children exposed to IPV are maternal mental health, the quality of the mother-child relationship, and maternal parenting skills, together with socioeconomic status (SES) and maternal level of education [32,33,[40][41][42][43][44][45][46][47][48].…”
Section: Empirical Evidence On Childhood Exposure To Ipvmentioning
confidence: 99%
“…Several studies using a person-centered approach have identified different profiles of adjustment among children and adolescents exposed to IPV, showing that between 15% and 60% of these population present profiles of resilience in absence of adjustment problems [33][34][35][36][37][38][39]. Across studies, the most significant and consistent factors discriminating between profiles of resilience and psychopathology in children exposed to IPV are maternal mental health, the quality of the mother-child relationship, and maternal parenting skills, together with socioeconomic status (SES) and maternal level of education [32,33,[40][41][42][43][44][45][46][47][48].…”
Section: Empirical Evidence On Childhood Exposure To Ipvmentioning
confidence: 99%
“…4 Recent studies suggest that 40% of 8-11 year old elementary school children reported having their life threatened 5 and 68% of adolescents have experienced at least one potentially traumatic experience in their lifetime 6 ranging from physical abuse, sexual abuse, and exposure to domestic or community violence. Moreover, children in vulnerable populations such as low-income urban youth and immigrant children have often been exposed to multiple traumatic events and secondary adversities.…”
Section: Multicultural Elementary Schools: Stakeholder Perspectives Omentioning
confidence: 99%
“…Definitions of early adversity have differed between studies. Physical, sexual or emotional abuse, divorce or separation of parents, incarceration of a parent, or domestic violence towards a parent are usually included, and these events have been shown to increase the risk for behavior problems and adult depression (Briggs-Gowan et al, 2010;Carter et al, 2010;Chapman et al, 2004). The experience of trauma such as war, sexual or violent physical assault, severe car accidents, natural disasters et c. has a well-known impact on mental health (Javidi and Yadollahie, 2012).…”
Section: Life Eventsmentioning
confidence: 99%